PENGARUH MODEL PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR SISWA SMAN 6 PURWOREJO DITINJAU DARI MOTIVASI BELAJAR - Lia Lestari; Cahyana Nursidiq; Cahyo Apri Setiaji (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Students’ learning outcomes in Economics subjects still show variation influenced by learning models and levels of learning motivation. This study aims to determine the differences in learning outcomes of tenth-grade students at SMA Negeri 6 Purworejo between those who participated in differentiated learning based on Project-Based Learning and those who followed conventional learning, the differences in learning outcomes based on high, moderate, and low levels of motivation, as well as the interaction between learning models and motivation in influencing learning outcomes. The population consisted of all tenth-grade students of SMA Negeri 6 Purworejo in the 2024/2025 academic year, totaling 249 students, with the sample determined using cluster random sampling. The research instruments included a learning motivation questionnaire with a Likert scale and an Economics achievement test that had been tested for validity and reliability. Data were analyzed using two-way ANOVA followed by post hoc tests. The results showed significant differences in learning outcomes between students who experienced differentiated learning based on Project-Based Learning and those who experienced conventional learning. In addition, there were differences in learning outcomes based on motivation levels, where highly motivated students achieved better results than students with moderate or low motivation. However, no interaction effect was found between learning models and motivation on learning outcomes. It can be concluded that differentiated learning based on Project-Based Learning is effective in improving students’ learning outcomes, particularly for those with high learning motivation.